2017
DOI: 10.1002/jctb.5442
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of pulsed electromagnetic fields from commercially available water treatment devices – controlled studies under static and flow conditions

Abstract: BACKGROUND Pulsed‐electromagnetic field (PEMF) devices are marketed and utilized for the non‐chemical management of biofouling, with little scientific validation of their effectiveness. Proof‐of‐principle studies were carried out previously to systematically investigate the effect of two such commercial devices on the culturability of bacteria under controlled static (i.e. non‐flowing) conditions and anti‐microbial effects were demonstrated. However, such effects were small and an expanded investigation, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Other studies have shown that the direct application of weaker electromagnetic fields (≤ 100 Hz; ≤ 1 mT) on bacterial cultures may have not only reductive [24, 25, 32], but also neutral [21, 34], or even stimulatory effects on bacterial cell growth [19, 20]. Interestingly, Piyadasa et al [35] reported that both stimulatory and inhibitory effects could be observed on the culturability of Escherichia coli and Pseudomonas fluorescence by 7 h exposure to pulsed electromagnetic fields under copiotrophic conditions. Latter authors showed that outcomes were influenced by water flow conditions (static vs. low flow vs. high flow) and differed between the two commercial devices used [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that the direct application of weaker electromagnetic fields (≤ 100 Hz; ≤ 1 mT) on bacterial cultures may have not only reductive [24, 25, 32], but also neutral [21, 34], or even stimulatory effects on bacterial cell growth [19, 20]. Interestingly, Piyadasa et al [35] reported that both stimulatory and inhibitory effects could be observed on the culturability of Escherichia coli and Pseudomonas fluorescence by 7 h exposure to pulsed electromagnetic fields under copiotrophic conditions. Latter authors showed that outcomes were influenced by water flow conditions (static vs. low flow vs. high flow) and differed between the two commercial devices used [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Piyadasa et al [35] reported that both stimulatory and inhibitory effects could be observed on the culturability of Escherichia coli and Pseudomonas fluorescence by 7 h exposure to pulsed electromagnetic fields under copiotrophic conditions. Latter authors showed that outcomes were influenced by water flow conditions (static vs. low flow vs. high flow) and differed between the two commercial devices used [35]. Therefore, we assume that the bacterial microbiota of circulatory systems may have been exposed to a different treatment regime, which induced temporarily an increase of colony counts, especially of heterotrophic bacteria growing at 36°C.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments of Piyadasa et al (2018) [84], it was observed that electromagnetic fields generate a great variety of positive or negative adaptive responses of different microorganisms, under various conditions. The interactions of some factors such as the type of microorganism, the specifications of the device generating the electromagnetic field (waveform, frequency, intensity, etc.…”
Section: Microbiological Effectsmentioning
confidence: 99%
“…TMFs, including PMFs and oscillating magnetic fields (OMFs), are an emerging non-thermal technique in the food processing industry [1, 2, 3], which can maximize the preservation of food appearance, flavour, texture, and nutritional quality, and improve the freezing process and quality of fresh ground beef [4], chicken breast [5], blueberries [6], cucumber [7], etc. In terms of bactericidal effect, PMF can be used to inhibit and destroy microorganisms such as Escherichia coli [8, 9, 10], yeast [11], and Staphylococcus aureus [12].…”
Section: Introductionmentioning
confidence: 99%